Interview: A colorectal surgeon's tale. (October 2012) - Phillips, Robin
Robin Phillips speaks to Ruth Williamson, Commissioning Editor: Professor Robin Phillips qualified at the Royal Free Hospital School of Medicine, London, UK, with higher surgical training completed in association with St Mary's Hospital Medical School, London, UK. Professor Phillips became a Consultant Surgeon at St Mark's Hospital in 1987 and has continued the appointment since. In addition, since 1993 Professor Phillips has been supported by the Imperial Cancer Research Fund (now CRUK) and is the Director of the St Mark's Polyposis Registry. In November 1999, Professor Phillips was appointed Civilian Consultant in Colorectal Surgery to the Royal Navy. Professor Phillips's research has predominantly been colorectal, mostly cancer, although with a maintained research interest in inflammatory bowel disease, anal fistulas and hemorrhoids. Here, Professor Phillips discusses his career to date, challenges in colorectal surgery and what we can look ahead to in the near future.